En-bloc Auriculectomy for Removal of a Large Pinna-Based Ear Mass in a Horse - Silverstone, Auri M.; Tatarniuk, Dane M.; Durket, Elyse; Gillen, Alex M. (Frontiers in Veterinary Science, 2020)
A 15-year-old Pony of America (POA) gelding presented for evaluation of a large mass present on the right external pinna. Based on gross appearance, the right ear mass was suspected to be neoplastic. The most likely differential diagnosis was that of a fibroblastic sarcoid. Complete auriculectomy via use of a constricting latex-tourniquet performed under multimodal analgesia was proposed as an option to achieve complete resolution of mass growth and improve patient comfort. Benefits of latex tourniquet constriction included immediate lack of bleeding associated with amputation, gradual ischemic necrosis and sloughing of tissue distant to the site of constriction, and cost-effective application. The external pinna sloughed three weeks following application of the constricting latex tourniquet. Complete healing was achieved within three months from the time of tourniquet application. The middle ear canal sealed closed as a result of auriculectomy, with no observed long-term discomfort or morbidity aside from reduction in hearing. This is the first report of total external ear amputation in the horse. Complete auriculectomy via use of a constricting latex tourniquet is a feasible method for en-bloc removal of large, complicated ear masses.